Ensuring equity in the era of HLA-restricted cancer therapeutics. Issue 11 (28th November 2022) - Smithy, James W; Blouin, Amanda; Diamond, Lisa C; Postow, Michael
Abstract : In January 2022, the US Food and Drug Administration granted regulatory approval to tebentafusp, a bispecific T cell receptor protein that targets melanoma antigen gp100 in the context of the human leucocyte antigen (HLA) A*0201 allele. This approval generated significant excitement, given the relative paucity of effective systemic therapies for advanced uveal melanoma. More broadly, tebentafusp represents the first T cell receptor agent to improve overall survival in any solid tumor. Although HLA-A*02:01 is the most common allele at this locus overall, its expression varies considerably among ethnic groups. It is most frequently expressed in Europeans, and less commonly in African Americans and people of Asian or Pacific Island ancestry. While uveal melanoma is most common in Caucasian populations, other HLA-restricted cancer therapeutics are being developed for indications with more diverse patient populations, such as cervical cancer. We advocate for proactive consideration of the populations eligible for each HLA-restricted therapeutic in development to ensure this emerging therapeutic class does not compound long-standing health disparities. As trials may focus on the most prevalent HLA subtypes, it will take the engagement of multiple stakeholders to ensure equitable access to patients of all ethnic backgrounds.